Sources of possible inoculum for horizontal transmission of nosema bombycis in diamondback moth, plutella xylostella (L.) - Idris, A. B; Grafius, E. (Universiti Kebangsaan Malaysia, 1999)
A study to identify possible sources of inoculum for horizontal transmission (within generation) of Nosema bombycis spores in diamondback moth (DBM), Plutella xylostella (L.), larvae were conducted. The body excretions (frass, silk, regurgitate and exuviae) of DBM larvae, and meconium of newly emerged DBM adults reared from Nosema-infected larvae were examined for N. bombycis spores. The presence and relative abundance of spores were observed microscopically. The effect of Nosema-contaminated Diadegma insulare (Cresson) on parasitism of DBM larvae was also investigated. Percentage infection and mortality of DBM larvae were used as evidence for the parasitoid's role in spore transmission among neonate DBM larvae. Results showed that all body excretions and the exuviae had N. bombycis spores or can be sources of Nosema spores. This suggests that these excretions are sources of N. bombycis spores for horizontal transmission. The spores were relatively more abundant in the late DBM instars than in the early instars. Percent infection and percentage mortality of DBM larvae parasitised by the Nosema-infected D. insulare was significantly higher when parasitism occurred in the early instars than in the late instars. Methods of avoiding N. bombycis infection in laboratory rearing of DBM are suggested. The importance of D. insulare as a major source for Nosema transmission and its possible diminishing role as biological control agent of DBM in the field are also discussed.